THE EFFECTIVENESS OF ENGLISH PODCASTS AND SONGS IN IMPROVING LISTENING SKILL OF INFORMATICS STUDENTS - Isnaeni, Resti (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2026)
Listening is one of the essential skills required by university students, including those majoring in Informatics, who must comprehend English-based learning resources such as documentation, tutorials, and technical discussions. This study aims to examine the effectiveness of English podcasts and English songs as alternative media to improve students’ listening comprehension. The research employed a quasi-experimental design involving 60 first-year Informatics students divided into an experimental group and a control group. The experimental group was exposed to English podcasts and songs for four weeks, while the control group used conventional listening materials from textbooks. Pre-test and post-test instruments were administered to measure performance changes. The findings revealed a significant improvement in the experimental group compared to the control group (p < 0.05), indicating that the integration of digital audio materials enhances vocabulary recognition, comprehension speed, and overall listening skill. This study suggests that educators incorporate podcasts and songs as complementary learning media in English instruction for Informatics students. ABSTRAK Keterampilan menyimak merupakan komponen penting dalam pembelajaran bahasa Inggris, terutama bagi mahasiswa Informatika yang sering berinteraksi dengan sumber belajar berbahasa Inggris seperti dokumentasi teknologi, video tutorial, dan diskusi teknis daring. Penelitian ini bertujuan untuk menguji efektivitas penggunaan podcast dan lagu berbahasa Inggris dalam meningkatkan kemampuan listening mahasiswa Informatika. Penelitian menggunakan desain kuasi-eksperimen dengan pre-test dan post-test yang melibatkan 60 mahasiswa tahun pertama, yang dibagi ke dalam kelompok eksperimen dan kelompok kontrol. Kelompok eksperimen memperoleh pembelajaran listening menggunakan podcast dan lagu, sedangkan kelompok kontrol menggunakan materi audio konvensional dari buku ajar. Hasil analisis statistik menunjukkan adanya peningkatan signifikan pada kemampuan menyimak kelompok eksperimen dibandingkan kelompok kontrol (p < 0.05). Mahasiswa yang belajar melalui podcast dan lagu menunjukkan peningkatan pemahaman, kecepatan menangkap informasi, serta penguasaan kosakata. Temuan ini menunjukkan bahwa media podcast dan lagu efektif digunakan sebagai alternatif pembelajaran listening dan direkomendasikan untuk diintegrasikan dalam pengajaran bahasa Inggris di program studi Informatika.